CFD SIMULATION OF THE DIRECT CHILL SEMI-CONTINUOUS CASTING PROCESS OF BRASS BILLETS - J; O; R (Интеллектуальные системы в производстве, 2009)
The modeling of semi continuous direct chill casting process has been used to investigate brass billets owing to its ability to produce high quality billets at relatively low operating costs. In this paper, a numerical study of transient flow phenomena such as free surface during the start-up phase is presented. The modeling of semi continuous casting process is concerned with the liquid/solid phase change problems in which three dimensional convective heat transfer in liquid metal has an effect on the growth of the solidified shell. The realistic model for start up phase of casting involves solidification drag modeling which has an important effect on solidification patterns within metallurgical zone of solidified brass billet. The software Flow3D has been used to model semi-continuous casting process of brass billets.